2015
DOI: 10.1111/jfb.12677
|View full text |Cite
|
Sign up to set email alerts
|

Farmed Atlantic salmon Salmo salar L. parr may reduce early survival of wild fish

Abstract: The study examined the density-mediated effects on growth, survival and dispersal of wild and farmed Atlantic salmon Salmo salar offspring in the period immediately following emergence, using a substitutive design. In small confined stream channels, wild parr coexisting with farmed parr had a significantly poorer survival, than wild parr alone. Density did not affect this relationship. In larger unconfined stream channels, wild parr coexisting with farmed parr entered a downstream trap in higher numbers than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
4
21
0
Order By: Relevance
“…ity and competition treatments among our wild families. This finding is consistent with that ofSundt-Hansen et al (2015) where fry with two farmed parents even had higher survival than fry with wild parents under conditions similar to those in our experiment. This was true both when they were alone (allopatry) and in competition (sympatry) with their wild half-siblings under near-natural conditions.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…ity and competition treatments among our wild families. This finding is consistent with that ofSundt-Hansen et al (2015) where fry with two farmed parents even had higher survival than fry with wild parents under conditions similar to those in our experiment. This was true both when they were alone (allopatry) and in competition (sympatry) with their wild half-siblings under near-natural conditions.…”
supporting
confidence: 93%
“…Combined with results from earlier studies Sundt-Hansen et al, 2015), this demonstrates that genetic introgression of farmed salmon may represent a direct cost to wild populations by imposing increased mortality on genetically wild individuals at the critical early life stage. That is, irrespective of maternal effects due to, for example, egg size differences between farmed and wild mothers.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Within the natural diet treatment wild fish had the lowest average survival. Sundt-Hansen et al [64] found that offspring of farmed salmon displaced and out-competed offspring of wild salmon in a short-term experiment conducted in a simulated stream environment, resulting in a lower survival of wild conspecifics. In the present study, food was presented in excess in each treatment to reduce or eliminate resource competition.…”
Section: Discussionmentioning
confidence: 99%